Local community participation in ecotourism development in Tasik Kenyir, Malaysia - Engku Hassan, Engku Nor Kamilah (IDOSI Publications, 2018)
Participation of local community in ecotourism has been highlighted and researched by many academics because it is a very important input for successful ecotourism development. This current study investigates the factors influencing the level of local community participation in ecotourism development in Tasik Kenyir, Malaysia. A quantitative approach is used in this research. The sample consists of 260 heads of household in three villages in Tasik Kenyir. The findings of the study indicate that four factors influence the level of participation in ecotourism development which include the family members’ involvement in ecotourism, perceived environmental impacts by the communities, marital status and the distance of residence to the ecotourism area. The study recommends that the local government ought to increase the accessibility for the local community to participate in ecotourism activities by including more representation of the community in the planning process; the study also suggests that future studies to explore factors like attitudes and readiness of the community that may influence the participation of the local community.